NOTAS SOBRE LA FLORA FOSIL DE LA ZONA DE TICO, PROVINCIA DE SANTA CRUZ. 5. Sphenopteris cf. goepperti Dunker 6. Cladophlebis sp. (Ameghiniana, 2013)
Some , fragmentary remains found in the locality Bajo Tigre, Ginkgoites tigrensis bed, are referred to Sphenopteris cf. goepperti Dunker and Cladophlebis sp. The first species has been found with delicate epidermis remains, which suggests a 'pteridophytic relation. A discussion on the previous records··of Rutfordia goepperti is presented.. The second species is found to be similar to Cladophlebis patagonica Frenguelli, although more material is needed to prove this identity